Whole exome sequencing identifies genetic markers of enterovirus susceptibility in East Asians - Sung, Chia-Cheng; Luxton, G. W. Gant; Hung, Kuo-Sheng; Wu, Yung-Fu; Wang, Chih-Chien; Hsu, Chih-Sin; Hu, Chih-Fen (Frontiers in Microbiology, 2024)
Following acute enterovirus (EV) infection, outcomes vary based on factors like the immune response, viral cell entry receptor expression levels, tissue tropism, and genetic factors of both the host and virus. While most individuals exhibit mild, self-limited symptoms, others may suffer severe complications or prolonged infections that can lead to autoimmune disorders. To elucidate host responses to EV infection, we performed whole exome sequencing on blood samples from both infected and uninfected individuals. Our initial focus was on genes encoding EV entry receptors—PSGL-1, SCARB2, and ANAXA2 for EV-A71, and CD155 for poliovirus—and on host genes ACBD3 and PI4KΒ, crucial for EV replication. Although no specific genetic variants directly associated with EV infection were identified, we discovered 118 variants across 116 genes enriched in East Asian populations through multi-layered variant filtering. These variants were further analyzed for their potential impacts on organs, biological processes, and molecular pathways. Phenome‐wide association studies were conducted to refine our understanding of their contributions to EV infection susceptibility. Our findings aim to develop a predictive panel based on these 118 variants, which could help susceptible individuals during EV outbreaks, guiding targeted clinical interventions and preventative strategies.